ENHANCEMENT OF SHOOTING PERFORMANCE THROUGH VISUAL MEMORY EXERCISES. A STUDY OF JUNIOR BASKETBALL ATHLETES - Atiyah, Zahid Hasan; Ferman, Saad Mahmood (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. In basketball, players have to observe many details very quickly within a shooting play; for example, they must note their own position on the court, the defender’s distance from them, the basket’s position, and their teammates' movements. Objectives. This paper indicates the role that higher visual memory plays in shooting accuracy (number of successful shots) among players (13-16) in a real game setting. Method. We conducted a descriptive correlational study that collected field data without changing the players’ basic training at all. The participants were 25 junior players aged 13-16 years with at least one year of experience and either normal or corrected vision. The players were subsequently divided into two groups: 11 players with high visual memory and 14 players with low visual memory. Results. The results showed a strong positive correlation (r=0.84, p<0.0001) between visual memory score and the number of successful shots. A correlation was also found between the average number of successful shots in the low and high visual memory groups. Player age was not correlated with visual memory score (p=0.18). Conclusion. There is a relationship between the average successful throws of the two categories, low memory and high memory, which proves the sub-hypothesis of the research. The player's age is not related to the degree of memory (P=0.18). The distributions of both memory score and aiming accuracy showed a concentration around the average values.